Inducing resistance in cotton against Colletotrichum gossypii var. cephalosporioides with essential oils - Santos, B. T.; Bulhões, C. C.; Bonaldo, S. M. (Scientific Electronic Archives, 2016)
This study aimed to evaluate the potential of essential oils of rosemary (Rosmarinus officinalis), baccharis (Baccharis trimera), lemon grass (Cymbopogon citratus), basil (Ocimum basilicum) and eucalyptus (Corymbia citriodora) in inducing resistance in cotton plants against C. gossypii var. cephalosporioides. The inductive effect of the essential oils was evaluated in plants growing in pots in the environment, which were treated with 1% essential oil at 47 days of age. 24 hours after elicitor treatment the plants were inoculated with a suspension of 1.5 x 105 conidia mL-1 of C. gossypii var. cephalosporioides. Five evaluations were performed disease and calculated the area under the disease progress curve. All essential oils showed potential for inducing resistance against cotton C. gossypii var. cephalosporioides.